THE EFFECT OF USING ANIMATION VIDEO FOR MENTALLY RETARDED STUDENTS IN VOCABULARY MASTERY - Pitaloka, Dinar; Thresia, Fenny; K, Fitri Palupi (Journal of English Education and Enterpreneurship (JEEP), 2021)
The aim of this research is to find out the influence and significant difference of using animation video for mentally retarded students’ vocabulary mastery at SLB Wiyata Dharma Metro. Animation video is a digital recording of an image, object and sound that moves across into or out of the screen, animation video also the rapid display of the sequences images that create an illusion of movement. This research used pre experimental research. The subjects of this research are the mentally retarded students at SLB Wiyata Dharma Metro academic year 2021. There are 5 students at 8 class C or mentally retardation class. The research instrument used to collect the data in this research is pretest and posttest. The result of data analysis indicates that the value of gain score obtained (0.76) was higher than gain score table (0.70). Then, the result of data analysis indicating the value of t obtained (3.70) was higher than t table (2.77) at the significance level 0.05 and the significance (0.020), and lower than 0.05. It can be concluded that there are influence and significant difference of using Animation Video in students’ vocabulary mastery.